Early Islam: the sectarian milieu of late antiquity? - Dye, Guillaume (Problèmes d'histoire des religions, 2022)
"In recent decades, new paradigms have radically altered the historical understanding of the Qur'an and early Islam, causing much debate and controversy. This volume gathers select proceedings from the first conference of the Early Islamic Sudies Seminar. These studies explore the history of the Qur'an and of formative islam, with the methodological tools set forth in Biblical, New Testament and Apocryphal studies, as well as the approaches used in the study of Second Temple Judaism, Christian and Rabbinic origins. It thereby contributes to the interdisciplinary study of formative Islam as part and parcel of the religious landscape of Late Antiquity,." --